From Values to Action : the Four Principles of Values-Based Leadership. - Kraemer, Harry M. (John Wiley & Sons, 2011)
Respected former CEO, professor, and speaker examines what it takes to become a values-based leader. In this highly-anticipated book, Harry Kraemer argues that today's business environment demands values-based leaders who, in "doing the right thing," deliver outstanding and lasting results. The journey to becoming a values-based leader starts with self-reflection. He asks, "If you are not self-reflective, how can you know yourself? If you do not know yourself, how can you lead yourself? If you cannot lead yourself, how can you lead others?" Kraemer identifies self-reflectio.